Il fondo di finanziamento ordinario - Nobili, Corrado; Turri, Matteo (Milano University Press, 2025)
The establishment of the Ordinary Financing Fund (Fondo per il finanziamento ordinario – FFO) for Italian state universities in 1993, with the redefinition of the mechanisms for allocating state resources among universities, marked a decisive turning point in the reform processes of the university system in Italy. Following an introduction to the main models of public funding, the volume focuses on performance-based funding (PBF), outlining its characteristics, strengths, and challenges. It then provides a diachronic reconstruction of the FFO, analyzing its transformations over time and their impact in terms of change. In conclusion, the effects of these changes in the funding system on the relationship between the state and universities, as well as on universities’ internal decision-making processes, are discussed.